PENGEMBANGAN FASILITAS WISATA TAMAN NARMADA KABUPATEN LOMBOK BARAT - Dolonseding, Fransisca Soffyana; Widiyani, Desak Made Sukma (Jurnal Anala, 2017)
Narmada Park is one of the cultural heritage sites that breathe Hinduism which is a historic relic of the entry of Hinduism on the island of Lombok. Narmada Park is also one of the tourist attraction with its main potential is the park, profane building which is a relic of Raja Anak Agung Gde Ngurah Karangasem and pond. The existence of Narmada Park is currently not widely known by the tourists who come to the island of Lombok, this causes the Park Narmada become one of the tourist attractions in Lombok with the number of visitors the smallest arrivals.The background of the small number of visitors who come to Narmada Park due to lack of visitor facilities, can be seen from the access of visitors who are not directed because many visitors who enter the area of Narmada Park through the entrance for the Hindus who will worship. Narmada Park tour route that has not been well arranged to cause visitors feel not directional when doing tours within the area of Narmada Park. The manager building that is not functioning properly causes maintenance of every area of the park is not maintained so that the beauty of the garden becomes reduced. This paper is a case study using the research method that is, the stage of formulating the initial idea, the initial idea maturation stage, the data collection phase through the literature study, field observation and interviews, the study area zoning stage, the data analysis phase, the data synthesis stage, and the design phase .The development of Narmada Park tourism facilities is expected to keep the heritage of the cultural heritage that has been, making Narmada become one of Lombok tourism destinations with facilities that can meet the needs of visitors, able to make visitors feel the feel of the kingdom as the former heyday, so that later can help improve the economy of local people .Keywords: facilities, cultural heritage, history, visitors, economy.